A new acotylean flatworm, Armatoplana colombiana n. sp. (Platyhelminthes: Polycladida: Stylochoplanidae) from the Caribbean coast of Colombia, South America - Bolaños, D. Marcela; Quiroga, Sigmer Y.; Litvaitis, Marian K. (Zootaxa, 2006)
Armatoplana colombiana n. sp. (Polycladida: Stylochoplanidae), a new species of acotylean flatworm from Colombia, is described. A. colombiana is characterized by 6–8 fleshy, anterior knobs, short nuchal tentacles, tentacular and cerebral eyes. A strongly muscularized, interpolated prostatic vesicle and a penis armed with a very long stylet places the species into the genus Armatoplana. The female reproductive system is characterized by the presence of a Lang’s vesicle and a sinuous vagina with rigid walls. Type material is deposited at the Museo de Historia Natural Marina de Colombia INVEMAR under INV-PLA 0019 and INV-PLA 0020 HS.